PELATIHAN PERAWATAN JENAZAH DI DESA GONDANGRAWE KECAMATAN ANDONG KABUPATEN BOYOLALI TAHUN 2025 - Suhadi, Imam; Hidayat, Muhammad Yunan; Isfihani, I; As-Sifa', Barik Pradana (AL HAZIQ: Journal of Community Service, 2025)
As leaders on earth, humans are required to help each other. No one can fulfill their own needs, everyone depends on others. Thomas Hobbes popularized the term Homo Homini Lupus, which means humans are wolves of other humans, and humans will eat other humans who are weaker. But there is also an opposite term, namely Homo Homini Socius, which means humans as social creatures who are friends with other humans, need each other, do not rely on themselves and carry out their roles according to their functions and duties. Islam as the religion of rahmatan lil alamin teaches us that a believer is a brother to another believer. For this reason, we need to help each other in goodness. Islam views the obligations of a believer towards other believers, one of which is in caring for his body, starting from washing, praying and burying. Islam teaches us ways to care for corpses that are in accordance with Islamic teachings and do not conflict with the Shari'a. For this reason, it is necessary to disseminate understanding, education and practice to the community on how to properly care for the bodies of Muslims.